Microplastisphere as a crowded and inclusive micro-ecosystem in seagrass meadow: Cross-kingdom connections and microbial food web - Qiqi Wu; Yu Xia; Yiwei Tao; Chengjun Ge; Yuanyuan Zhao; Dan Feng; Hui Deng (Marine Pollution Bulletin, 2026)

Evolution of cracks in red-bed mudstone under the coupling of drying-wetting cycle and temperature: From microscopic mechanism to a kinetic model - Guodong Zhang; Sixiang Ling; Chengjun Xiao; Hongwei Liu; Xiaoning Li; Rui Deng; Xiyong Wu (Engineering Geology, 2026)

Dark side of biodegradable microplastics in mangrove ecosystem: Plastisphere as an overlooked hotspot of sulfate-reducing metabolism - Yiqiao Zheng; Qiqi Wu; Yu Xia; Hui Deng; Yuanyuan Zhao; Jiwei Luo; Dan Feng; Chengjun Ge (Water Research, 2026)

A critical review of microbial electrochemical systems for uranium remediation: Bioelectrochemical reduction, resource recovery, and sustainability considerations - Jingyi Wang; Ziyin Xia; Liyao Zeng; Leyi Chen; Yiming Jiang; Guanzhen Chen; Chengjun Guo; Jiaqian Zhang; Weiquan Deng; Chenxi Li; Meng Li; Hongguo Zhang (Journal of Environmental Chemical Engineering, 2026)

Microplastics drive the reconfiguration of microbial sulfur cycling pathways in seagrass bed sediments - Mingguang Luo; Jinluo Fan; Xiujun Wang; Yibing Ge; Dan Feng; Shengkai Cao; Jun Wang; Hui Deng; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge; Honglin Bu (Environmental Pollution, 2026)

Long-term natural photodegradation of plastic films enhances the molecular complexity of plastic-derived dissolved organic matter - Derong Zhang; Jiwei Luo; Xue Li; Dongming Wu; Yanhai Xie; Hui Zeng; Hui Deng; Qingmian Chen; Chengjun Ge; Ying Zhang (Water Research, 2026)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Colonization time of plastisphere drives the dynamics of organic carbon stability and microbial communities in seagrass bed sediments - Shuailing Hou; Jun Wang; Dan Feng; Dongming Wu; Shiquan Chen; Jinluo Fan; Mingguang Luo; Hui Deng; Xing Yang; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge (Journal of Hazardous Materials, 2025)

Claudin-11 plays a pivotal role in the clathrin-mediated endocytosis of influenza A virus - Xiaofei Yu; Zixin Ni; Yifan Wang; Jingfei Wang; Guohua Deng; Jianzhong Shi; Huihui Kong; Yongping Jiang; Guobin Tian; Chengjun Li; Yoshihiro Kawaoka; Hualan Chen; et al. (Science China Life Sciences, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

Adverse effects of microplastics on the growth, photosynthesis, and astaxanthin synthesis of Haematococcus pluvialis - Weibin Zhao; Jiaye Deng; Jiamei Wang; Chengjun Ge; Hui Yang (Science of The Total Environment, 2024)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Integrated microbiota and multi-omics analysis reveal the differential responses of earthworm to conventional and biodegradable microplastics in soil under biogas slurry irrigation - Yuanyuan Zhao; Huiting Jia; Hui Deng; Chengjun Ge; Wenzhe Xing; Huamei Yu; Jiatong Li (Science of The Total Environment, 2024)

Integrated microbiome and multi-omics analysis reveal the molecular mechanisms of Eisenia fetida in response to biochar-derived dissolved and particulate matters - Huiting Jia; Yuanyuan Zhao; Hui Deng; Huamei Yu; Chengjun Ge; Jiatong Li (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Black phosphorus nanosheets enhance differentiation of neural progenitor cells for improved treatment in spinal cord injury - Fumei He; Ke Cheng; Junyang Qi; Fangjie He; Chengjun Chu; Yue Xiong; Jingxin Zhao; JiaQi Ding; FanShu Kong; ZiMeng Cao; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Response of earthworms to microplastics in soil under biogas slurry irrigation: Toxicity comparison of conventional and biodegradable microplastics - Yuanyuan Zhao; Huiting Jia; Hui Deng; Wenzhe Xing; Dan Feng; Jiatong Li; Chengjun Ge; Huamei Yu; Ying Zhang; Haiying Chen (Science of The Total Environment, 2023)

Design of Control System for Multistage Distillation Seawater Desalination Device Driven by Photovoltaic-Thermal - Jiaqi Yan; Chengjun Qiu; Yuangan Wang; Ning Wu; Wei Qu; Yuan Zhuang; Guohui Yan; Ping Wang; Ruoyu Zhang; Yirou Yan; Ruonan Deng; Jiuqiang Luo; et al. (Journal of Marine Science and Engineering, 2023)
This research proposes a seawater desalination system driven by photovoltaic and solar thermal energy for remote regions such as islands and seaside villages where fresh water is not accessible. The performance of this system is demonstrated through experiments, and the main concerns are the output of the photovoltaic power generation system, power quantity, water yield, and the loads under different solar irradiance and temperature. In this system, a PLC is used as the controller to adjust the water pump by the collection and processing of sensor data. A load switching time system is designed to select different operating schemes under different environments in order to save energy. The control method of this system is developed to ensure that the photovoltaic power generation system does not undervoltage while maintaining the normal operation of the desalination system. An improved Perturbation and Observation (P&O) algorithm is also proposed as a new Maximum Point Power Tracking (MPPT) method to solve the problem of misjudgment and oscillation after tracking the maximum power point (MPP) in the traditional P&O algorithm. The simulation test in the MATLAB/Simulink environment shows that when external irradiance changes, the improved P&O algorithm can track the MPP faster than the traditional P&O algorithm, and the amplitude of oscillation on the MPP is smaller. The hardware experiments show that this system can operate stably and flexibly, and it is capable of producing 5.18 kWh of electric energy and 335.81 kg of freshwater per day. The maximum yield of the unit can reach 565.75 kg per day and the maximum daily power generation is 8.12 kWh.

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Vaccination of poultry successfully eliminated human infection with H7N9 virus in China - Xianying Zeng; Guobin Tian; Jianzhong Shi; Guohua Deng; Chengjun Li; Hualan Chen (Science China Life Sciences, 2018)

Molecular structure of glycogen in diabetic liver - Bin Deng; Mitchell A. Sullivan; Jialun Li; Xinle Tan; Chengjun Zhu; Benjamin L. Schulz; Robert G. Gilbert (Glycoconjugate Journal, 2015)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)